HUBUNGAN PENGETAHUAN IBU TENTANG ISPA DENGAN PERAWATAN ANAK ISPA 1-5 TAHUN DI RUMAH - Susilowati, Susilowati; Anggraeni, Niken (Akademi Keperawatan Pamenang, 2012)
Acute Upper Tract Infection (ISPA) is a respiratory infection that are anatomically differentiated upper respiratory starting from the nose to the alveoli caused by infecting agents that cause respiratory tract inflammation reactions involved. ISPA is one of the commonest causes of death in children in developing countries. Acute Respiratory Tract Infection is caused four of the 15 million estimated deaths in children under the age of five years each him. Home care is very important in the management of children with respiratory tract infections in the majority of children can be cured by treatment with a good home. The purpose of this research is to know the relationship with the mother knowledge about ISPA levels 1-5 years child care at home in the area of PHC Gampengrejo Pustu Plosorejo Kediri in 2010. This research design is cross sectional analytic, samples taken from mothers who have children ages 1-5 years at ARI Pustu Plosorejo 30 people with large samples of respondents with a simple random sampling technique using questionnaire research instruments. From the results of Spearman correlation test showed significance (p) = 0.000 and Î± = 0.05 then p <Î± means that Ho refused and H1 accepted, so we can conclude there is a correlation between knowledge of mothers regarding ARI and ARI level of child care at home 1-5 years. To increase the level of child care at home 1-5 years ARI, can be done by providing health education, and for the parents can better explore the information by various media that exist primarily on ARI in children aged 1-5 years. Â Keywords: Knowledge, Treatment of ARI children at home